2023
DOI: 10.1111/sms.14376
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb cranking asymmetry during a Wingate anaerobic test in wheelchair basketball players

Abstract: Introduction Interlimb asymmetry of strength and/or motor coordination could limit the performance of wheelchair athletes or increase their risk of injury. Studies of interlimb asymmetry in the lower limbs have shown high between‐subject variability that does not depend on the side of dominance and that does not change with fatigue. Upper limb asymmetry is particularly large in manual wheelchair athletes with a lower degree of impairment. The aim of this study was to evaluate interlimb asymmetry of forces deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the sport-specificity of the impact of interlimb asymmetry is noteworthy. Brassart et al (2023) focused on wheelchair basketball players, revealing that upper limb asymmetry could hinder performance or increase injury risk, particularly in athletes with lower degrees of impairment. This suggests that the influence of asymmetry might be modulated by the functional status of the athlete.…”
Section: Literature Review 1 Interlimb Strength Asymmetry: Impact On ...mentioning
confidence: 99%
“…Moreover, the sport-specificity of the impact of interlimb asymmetry is noteworthy. Brassart et al (2023) focused on wheelchair basketball players, revealing that upper limb asymmetry could hinder performance or increase injury risk, particularly in athletes with lower degrees of impairment. This suggests that the influence of asymmetry might be modulated by the functional status of the athlete.…”
Section: Literature Review 1 Interlimb Strength Asymmetry: Impact On ...mentioning
confidence: 99%
“…To prevent movement between the participant and the wheelchair and between the wheelchair and the floor during the test, each participant was strapped at their thighs or hips according to their pathologies, and their wheelchair were fixed with ratchet straps to the floor. The axis of rotation of the cranks was aligned with the glenohumeral joint [22,25]. The warm-up consisted of 3 min of self-selected cadence cranking at a resistance of 25 W followed by 3 min of low-intensity interval work with active rest periods (working and resting resistance of 100 and 15 W, respectively).…”
Section: Protocols and Materialsmentioning
confidence: 99%
“…The arm ergometer software used a torque factor (TF) to establish the resistance level, which was calculated as the torque value divided by the participant's body mass. To individualize the resistance for each participant, an isokinetic test was performed at 80 RPM for 5 s at peak power, and the maximum torque developed was normalized by the participant's body mass to obtain the TF at peak power (TF-ISO) [22]. The resistance levels for each participant were established as 80% of TF-ISO, 40% of TF-ISO, and 0% of TF-ISO.…”
Section: Protocols and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of asymmetries between the limbs has been studied, with few studies specifically addressing performance [ 7 ]. Similarly, it has been reported that limb dominance influences movement kinematics, or is influenced by specific activity, as certain modalities place greater demands on one side of the body and highlight the dominant side compared to the non-dominant limb [ 8 ].…”
Section: Introductionmentioning
confidence: 99%